Soap Operas and the (in) contestable use of steotypes (Intercom - Brazilian Journal of Communication Sciences, 2025)
Stereotypes are “solid impressions”, positive or negative, associated with a certain reality or social group. They are mental patterns, derived from individuals’ value systems, which result from processes of simplification and generalization of certain common characteristics. The aim of this article is therefore to find out whether soap operas inherit the almost always inevitable use of stereotypes from the environment in which they are set: is there a tendency for soap operas to be linked to or to distance themselves from this representative tool? In order to answer these questions, this article analyzes the episodes of two Portuguese soap operas, conducts semi-structured interviews with their scriptwriters and holds a focus group.
Keywords: Soap operas; stereotypes; television; reality; identification